Geriatric syndromes predict mortality of people aged 75+ years in the observation room of emergency department: Towards function-centric emergency medicine. (May 2022) - Huang, Hsien-Hao; Lin, Pei-Ying; Chen, Tze-Yin; Wang, Tse-Yao; Chang, Julia Chia-Yu; Peng, Li-Ning; Yen, David Hung-Tsang
Highlights: Both malnutrition and CCI were the independent predictors of mortality after 3-month and 6-month of follow-up. The other independent predictors of mortality after the 3-month and the 6-month follow-up were incontinence and ADL, respectively. For emergency doctors, the function-centric survey of geriatric syndrome might help to screen the discharged non-critically ill older old ED patients after 3-month and 6-month follow-up. Abstract: Background: Aging is a complex process involving functional decline, reduced physiological reserve, increased multimorbidity, and impaired homeostasis, all of which collectively generate various health risks for older adults. To predict short-term mortality of non-critical older patients in the observation room of the emergency department (ED) based on function-centric approach instead of disease-centric one. Methods: We conducted a prospective study enrolling 831 patients aged 75 years and older between 2018 and 2020. Comprehensive geriatric assessment was performed on all patients, and the results were integrated into the care planning process. Results: In total 831 patients (mean age: 84.8 ± 5.8 years) were enrolled and the post-discharge mortality rate was 3.3% (28 deaths) after 3 months, and 5.4% (45 deaths) after 6 months. The independent predictors of 3-month mortality were malnutrition (adjusted odds ratio [OR], 4.77; p  < 0.05), incontinence (adjusted OR, 2.58; p  < 0.05) and multimorbidity (adjusted OR, 1.51; p  < 0.001). For 6-month mortality, malnutrition (adjusted OR, 4.20; p  < 0.01), multimorbidity (adjusted OR, 1.40; p  < 0.001) and activities of daily living (adjusted OR, 0.99; p  < 0.05) were all independent predictors. Conclusion: Although ED aims to treat acute and life-threatening conditions, older persons with geriatric syndromes are also at a substantially high risk of adverse outcomes, even mortality. Transitioning of the ED from disease-centric to function-centric services is important for responding to the changing health care needs of super-aged societies.